Cohesion Policy - an Essential Pillar for the Achievement of the Objectives of Europe 2020 Strategy - Andreea Drăgoi (Revista de Economie Mondială, 2014)
Since its creation, through the establishment in 1958 of the two sectoral funds - European Social Fund (ESF) and the European Agricultural Guidance and Guarantee Fund (EAGGF), Cohesion Policy has acted as a payment mechanism for redistribution of budgetary contributions between Member States in order to reduce regional development disparities between them. The main items discussed in this article are the objectives and mechanisms of the Cohesion Policy, the evolution of budget allocations and main pillars of this common policy reform. Our paper also proposes a comparative analysis between the objectives of the new funding framework of the Cohesion Policy for the period 2014 - 2020 and the annual allocations in 2007-2013, with a focus on "lessons learned" and the congruence of this common policy objectives to those of Europe 2020 Strategy.